2020
DOI: 10.1111/hsc.13245
|View full text |Cite
|
Sign up to set email alerts
|

What is the impact of day care on older people with long‐term conditions: A systematic review

Abstract: Day care for older people provide opportunities for social contact and social support (Lecovich & Biderman, 2012) and can support health, nutritional and daily living (Anderson et al., 2012). Perceived benefits are associated with improved mental health, socialisation, physical function and quality of life (Orellana, Manthorpe, & Tinker et al., 2018).Day care models are mixed and often involve complex arrangements (Gridley, Brooks, & Glendinning, 2012). Internationally, access to day care may be linked to nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 62 publications
1
19
0
1
Order By: Relevance
“…This perhaps explains the lack of research about cost-effectiveness (Ellen et al, 2017). The present study and Lunt's (2018) were able only to report attendance charges, and even these are not often publicly available (Green et al, 2021). Apart from the Personal Social Services Research Unit's annual Unit Costs work, which covers local authority day care provision (https://www.pssru.ac.uk/project-pages/unit-costs/), only one English study has reported income streams and nancial viability of 12 day centres for people with disabilities while operating as social enterprises (Powell, 2015;Powell et al, 2019).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This perhaps explains the lack of research about cost-effectiveness (Ellen et al, 2017). The present study and Lunt's (2018) were able only to report attendance charges, and even these are not often publicly available (Green et al, 2021). Apart from the Personal Social Services Research Unit's annual Unit Costs work, which covers local authority day care provision (https://www.pssru.ac.uk/project-pages/unit-costs/), only one English study has reported income streams and nancial viability of 12 day centres for people with disabilities while operating as social enterprises (Powell, 2015;Powell et al, 2019).…”
Section: Discussionmentioning
confidence: 82%
“…Numbers of people living alone are increasing, especially among the oldest old (Kempton & Tomlin, 2014). Many day centre attenders live alone (Lunt, 2018;BLINDED 2020a). People ageing without children, an increasing group (ONS, 2020), felt extremely isolated during the pandemic with the withdrawal of group activities (Collieson, 2021) and face additional disadvantage as much practical support is from adult offspring (Pickard et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…10,11 и национальном проекте «Демография» 12 . С 2018 г. в стране реализуется пилотный проект по созданию системы долговре менного ухода, целью которого выступает повышение доступности и улучшение качества ухода для лиц с ограничениями в автономности, что, как показывает зарубежный опыт, может стать фактором снижения заболеваемости и смерт ности в старших возрастах [Choi, Joung, 2016;Lunt, Dowrick, Lloyd-Williams, 2021]. С 2019 г. начато повышение пенсионного возраста и введены меры дополни тельной защиты занятости граждан предпенсионного возраста и содействия в их трудоустройстве.…”
Section: государство и обществоunclassified
“…Latent class analyses (LCA) have been popular in recent years to identify subgroups based on estimated posterior membership, such as pattern of HCBS use (Wang et al, 2021). Thus, researchers have recently begun focusing on the impacts and outcomes of HCBS use patterns instead of evaluating effects of single-type HCBS (Han et al, 2021;Igarashi et al, 2017;Jorgensen et al, 2018;Lunt et al, 2020;Rahman et al, 2019;Wang et al, 2021;Yu et al, 2020). Most studies exploring the effects of different patterns of multiple HCBS use, however, have preliminarily focused on nursing home admission (Jorgensen et al, 2018;Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%